Evaluation of advanced receiver autonomous integrity monitoring performance on predicted aircraft trajectories - Paternostro, S.; Moore, Terry; Hill, Chris; Atkin, Jason; Morvan, Herve (2016)
The development of new GNSS constellations, and the modernization of existing ones, has increased the availability and the number of satellites-in-view, paving the way for new navigation algorithms and techniques. These offer the opportunity to improve the navigation performance while at the same time potentially reducing the support which has to be provided by Ground and Satellite Based Augmented Systems (GBAS and SBAS). These enhanced future capabilities can enable GNSS receivers to serve as a primary means of navigation, worldwide, and have provided the motivation for the Federal Aviation Administration (FAA) to form the GNSS Evolution Architecture Study (GEAS). This panel, formed in 2008, investigates the new GNSS-based architectures, with a focus on precision approach down to LPV-200 operations. GEAS identified ARAIM as the most promising system. The literature, produced through a series of studies, has analysed the performance of this new technique and has clearly shown that the potential of ARAIM architectures to provide the Required Navigation Performance for LPV 200. Almost all of the analysis was performed by simply studying a constellation’s configuration with respect to fixed points on a grid on the Earth’s surface, with full view of the sky, evaluating ARAIM performance from a geometrical point of view and using nominal performance in simulated scenarios lasting several days In this paper, we will evaluate the ARAIM performance in simulated operational configurations. Aircraft flights can last for hours and on-board receivers don’t always have a full view of the sky. Attitude changes from manoeuvers, obscuration by the aircraft body and shadowing from the surrounding environment could all affect the incoming signal from the GNSS constellations, leading to configurations that could adversely affect the real performance. For this reason, the main objective of the algorithm developed in this research project is to analyse these shadowing effects and compute the performance of the ARAIM technique when integrated with a predicted flight path using different combinations of three constellations (GPS, GLONASS and Galileo), considered as fully operational.